The Lateral Fibular Stress Test: High Variability of Force Applied May Lead to Under-Detection of Syndesmotic Instability. Issue 4 (November 2022) - Ingall, Eitan M.; Kaiser, Philip; Ashkani-Esfahani, Soheil; Zhao, John Z.; Kwon, John Y.
Category: Ankle Introduction/Purpose: The lateral fibular stress test (LFST), also known as the hook or Cotton test, is commonly performed to assess syndesmotic instability intraoperatively. Several studies have determined that 100 Newtons (N) is the required force applied when performing the LFST to detect syndesmotic instability. We hypothesize that surgeons do not uniformly nor consistently apply 100N of force when performing the LFST and that substantial variation exists. Fundamentally, this could lead to under-detection of syndesmotic instability as surgeons may not be applying the requisite force in a consistent manner. Methods: A biomechanical SawBones lower leg model including simulated soft tissue envelope (SawBones inc., Vashon Island, Washington) was mounted to a board and a 1cm diameter hole was drilled across the tibia and fibula in the area of the syndesmosis. An industrial force gauge (Nidec-Shimpo, Kyoto, Japan) was then mounted. A metal extension piece was passed from the force gauge through the hole and positioned so that the tip was exposed on the lateral side of the model. A commonly utilized reduction clamp was affixed to the force gauge. Orthopaedic attending surgeons and trainees were asked to perform a series of LFSTs and to simulate the force they typically apply intra-operatively and this force was recorded in Newtons (N). Basic demographic data was collected on each participant. Results: 33 surgeons participated in the study, including 18 trainees. The median (IQR) force applied during the LFST was 96.42(71.42-126.33), 87.49 (69.19-117.40), 99.99(79.91-137.49), for the pooled group, attendings, and trainees respectively. Over half (54.5%) of all trials were less than 100N (57.8% of surgeons, 51.8% trainees). The distribution of pulls is shown in Figure 1. Intraobserver correlation was excellent within the overall cohort (0.92, p<0.001), trainees (0.90, p<0.001) and attendings (0.94, p<0.001), respectively. Inter-observer reliability was fair among the overall cohort (Kappa =0.28, p=0.49), and poor between the attendings (Kappa=0.11, p=0.69), and the trainees (Kappa=0.05, p=0.82), respectively. Conclusion: Our study demonstrates that the amount of lateral force applied by surgeons in a biomechanical ankle model when performing the LFST is variable and often less than 100N. Inadequate force application when performing the LFST may lead to under-detection of syndesmotic instability which may portend a poorer outcome. Either the intraoperative use of force gauges and/or specific practice outside of the operating theatre (to become familiarized with the proprioceptive feel of generating the requisite force) may permit surgeons to consistently apply the test in a manner that is clinically reproducible.